ANALISA PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN SEPEDA MOTOR HONDA - Agustim, Warter (Jurnal Ekonomi Modernisasi, 2010)
Nowadays the rivalry of motorcycle industry in Indonesia increases rapidly. In facing this condition, the motorcycle producers are demanded to form a strong competitive superior component by making a good brand image for consumers. Brand image is a trade mark association; it is formed and stuck on consumers’ mind. It has three components i.e. producer, consumer, and product image. This research aimed to find out and analyze the affect of brand image consisted of producer, consumer, and product image to the consumers’ decision in buying Honda motorcycle, both in partially and simultaneously to find out which variables had domain effect. The type of this research is explanatory research explaining the causal relationship among variables by using hypothesis test. The sample of this research was 69 S-1 students of Economic Faculty of Tribhuwana Tunggadewi University of Malang; they had ever bought Honda motorcycle. The data analysis method used in this research was multiple linier regressions.  The result gained by using multiple linier regressions showed that both in partially and simultaneously producer image variable (X1), consumer image (X2), and product image (X3) had a significant effect to the consumers decision in buying Honda motorcycle. Whereas, the variable which was dominant to the consumers was product image variable (X3).            The conclusion which could be taken from this research was the three independent variables i.e. producer image, consumer image, and product image both in partially and simultaneously had a significant effect to the consumers’ decision in buying Honda motorcycle. Product image variable (X3) was the variable having a dominant effect to the consumers’ decision in buying Honda motorcycle. By having know that brand image had a significant effect to the consumers’ decision, it was suggested that Honda Company could maintain its brand image formed nowadays so that it could increase the sale of Honda motorcycle